Total Anomalous Pulmonary Venous Connection with Lethal Pulmonary Venous Obstruction Managed by Multidisciplinary Cooperation - Kana Ito; Ayako Chida-Nagai; Osamu Sasaki; Nobuyasu Kato; Takeshi Umazume; Satoshi Kawaguchi; Kazutoshi Cho; Gaku Izumi; Hirokuni Yamazawa; Atsuhito Takeda (Hindawi Limited, 2021)
Background. Total anomalous pulmonary venous connection (TAPVC) is a critical congenital heart disease for which emergency surgery is required after birth. In cases of no intervention, TAPVC is associated with a high mortality rate in the first year of life. Although foetal echocardiographic techniques for diagnosing TAPVC have improved, TAPVC remains one of the most difficult congenital heart diseases to diagnose via foetal echocardiography. Here, we report a case of TAPVC with pulmonary venous obstruction (PVO), which was diagnosed via foetal echocardiography. Case Presentation. On foetal echocardiography at 32 weeks' gestation, a large atrial septal defect, enlarged superior vena cava, and continuous flow pattern in the vertical vein from the common chamber were observed in the foetus. Paediatric cardiologists and cardiac surgeons, neonatologists, and obstetricians planned to perform a caesarean section and emergency heart surgery. The male infant was born at 37 weeks' gestation via caesarean section, and postnatal echocardiography revealed PVO at the confluence of the superior vena cava and common chamber. Similarly, chest computed tomography confirmed the foetal diagnosis. The postnatal diagnoses were TAPVC type Ib, PVO, atrial septal defect, and patent ductus arteriosus. Surgical repair of the TAPVC was initiated within the first 3 hours of life. Screening brain echocardiography and head computed tomography revealed intracranial haemorrhage and hydrocephalus. Therefore, the patient underwent emergency bilateral external drainage on day 13. On day 48, a ventriculoperitoneal shunt was inserted owing to progressive brain ventricular dilatation. The patient was discharged home on postoperative day 68. Conclusions. Although the prognosis of TAPVC with PVO remains poor, continuous observation through foetal echocardiography and early interdepartmental collaboration can result in good outcomes.